Pemberdayaan Komunitas melalui Pelatihan Kewirausahaan di Panti Asuhan Al-Hikmah Kota Semarang - Anindya Auliasari; Apriya Sani Maulina; Dewi Nabela Sofya El-Fikri; Siti Hikmah (Lembaga Pengembangan Kinerja Dosen, 2024)
An orphanage is an institution that houses children who do not have families or children who cannot live at home with their families. In addition, the orphanage is also engaged in the social field, namely helping children who are neglected and no longer have parents. The location of community service was carried out at Al-Hikmah Orphanage Semarang from October 26 to December 1, 2024. The research subjects amounted to 10 children with specific characteristics, namely children who live in orphanages and are in the age range of 13-18 years, equivalent to the MTs and MA education levels. Based on the research results that have been described in the conclusion, we as researchers in this study propose the following suggestions: (1) For the Al-Hikmah Orphanage: Can consider making entrepreneurship training a routine activity that can be a forum for children in developing and practicing their entrepreneurial skills, this activity can be in the form of a weekly workshop or a project with a long-term time. (2) For future researchers: It is expected to develop a more specific entrepreneurship training model and of course by adjusting the existing technological developments, for example by conducting technology-based entrepreneurship training